Sydney Anglicans and the threat to world Anglicanism the Sydney experiment - Porter, Muriel (Burlington, VT : Ashgate Pub., 2011)
Sydney Anglicans, always ultra-conservative in terms of liturgy, theology and personal morality, have increasingly modelled themselves on sixteenth century English Puritanism. Over the past few decades, they have added radical congregationalism to the mix. Under Archbishop Peter Jensen they have become prominent in the leadership of the global movement that is threatening worldwide Anglican unity. Porter unpacks how Australia's largest diocese developed its ideological fervour and explores the impact it is having both in Australia and the Anglican Communion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Anglican Church of Australia. -- Diocese of Sydney; Conservatism -- Religious aspects -- Anglican Communion; Anglican Church of Australia. Diocese of Sydney; Anglican Church of Australia. -- Diocese of Sydney; Conservatism -- Religious aspects -- Anglican Communion; Conservatism; Religion; RELIGION / Christian Theology / Ecclesiology; Electronic books